2002
DOI: 10.1088/0305-4470/35/49/303
|View full text |Cite
|
Sign up to set email alerts
|

On generalized scaling laws with continuously varying exponents

Abstract: Many physical systems share the property of scale invariance. Most of them show ordinary power-law scaling, where quantities can be expressed as a leading power law times a scaling function which depends on scaling-invariant ratios of the parameters. However, some systems do not obey power-law scaling, instead there is numerical evidence for a logarithmic scaling form, in which the scaling function depends on ratios of the logarithms of the parameters. Based on previous ideas by Tang we propose that this type … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…22 According to Ref. 27, the physical origin of logarithmic scaling is associated with multifractality and local scaling invariance. To the best of our knowledge, the results presented above are the first numerical confirmation of the scaling relation (4), in which the scaling variable is given by the ratio of the logarithm of the system width L to the logarithm of the correlation length ξ, instead of the ratio L/ξ as applied usually.…”
Section: Discussionmentioning
confidence: 99%
“…22 According to Ref. 27, the physical origin of logarithmic scaling is associated with multifractality and local scaling invariance. To the best of our knowledge, the results presented above are the first numerical confirmation of the scaling relation (4), in which the scaling variable is given by the ratio of the logarithm of the system width L to the logarithm of the correlation length ξ, instead of the ratio L/ξ as applied usually.…”
Section: Discussionmentioning
confidence: 99%
“…[5] it was suggested that for PLD this quantity follows an unusual logarithmic scaling. Later this type of scaling behavior was explained in the framework of scaling laws with continuously varying exponents [14]. Opposed to these early conjectures, we present numerical evidence that such logarithmic scaling laws do not hold asymptotically, although they may be used as a good approximation.…”
Section: Introductionmentioning
confidence: 52%
“…8 shows a data collapse of the normalized nucleation density according to this scaling form, which at first glance seems to be convincing. Initially it was speculated that the unusual type of scaling behavior, which can be explained in terms of continuously varying critical exponents [14], may be related to the fractal structure of the islands, which become more and more compact as the first monolayer is filled up. However, later it was shown [7] that the same logarithmic scaling form can be used in a 1+1-dimensional model for pulsed deposition, where the (one-dimensional) islands are always compact.…”
Section: Scaling Properties Of Pulsed Depositionmentioning
confidence: 99%
“…Such intrinsic properties in the systems' equations can lead to intriguing and interesting dynamical consequences (Lai, 1997). Many physical systems share the property of scale invariance, most of them show ordinary power-law scaling, where quantities can be expressed as a leading powerlaw scaling function which depends on scalinginvariant ratios of the parameters (Sittler and Hinrichsen, 2002). For example, earthquakes, proteins, the wealth of nations and stock market cracks.…”
Section: Fractal Mathematicsmentioning
confidence: 99%
“…In other words, the question is how much isomorphism in there between the real systems and its fractal model. Such systems do not obey power-law scaling; instead there is numerical evidence for a logarithmic scaling form, in which the scaling function depends on ratios of the parameters' logarithms (Sittler and Hinrichsen, 2002). Perhaps the most important practical aspect of fractal analysis may be the use of fractal dimension as a quantitative variable that morphologists can study as a dependent variable in the context of many independent variables (Klonowsk, 2000).…”
Section: Fractal Mathematicsmentioning
confidence: 99%